The Influence of Resettlement of the Capital of Probolinggo Regency Toward Service Quality of Police Record (SKCK) (Study in Probolinggo Resort Police) - Erlinda Puspitasari; Mardiyono Mardiyono; Hermawan Hermawan (Sekolah Pascasarjana Universitas Brawijaya, 2013)
This study examined the influence of resettlement of the capital of Probolinggo Regency toward service quality of Police Record (SKCK) in Probolinggo Resort Police. Probolinggo Resort Police (Polres) is one government agencies that experiencing resettlement of the location from Probolinggo City to Kraksaan district. It is expected that by this resettlement, public service processes would become ‘better and in high quality’. The study used quantitative research method with explanatory approach to test the hypothesis that has been set. Dependent variable in this study are resettlement of the capital of regency (X) with the variables: affordability, recoverability and replicability. While the dependent variable in this study are the service quality of Police Record (SKCK) (Y) with the indicators: tangibles, reliability, responsiveness, assurance and empathy. The study used multiple linear regression method of analysis. The study revealed that the resettlement of the capital of regency variable (X) which consist of three variables such as affordability (X1), recoverability (X2) and replicability variable (X3) influence significantly toward service quality of the Police Record (SKCK) in Probolinggo Resort Police (Polres). Keywords: The Resettlement, The Capital of Regency, Service Quality, Police Record (SKCK), Probolinggo Resort Police.